2022
DOI: 10.1155/2022/6686931
|View full text |Cite
|
Sign up to set email alerts
|

The Mitigatory Effect of Shen-Qi Compound on the Diabetic Thoracic Aortic Complications through Inhibiting the Inflammatory Microenvironment by miR-223-3p/RBP-J/IRF8 Axis

Abstract: Background. Disruption of the vascular immunological inflammatory microenvironment is linked to metabolic memory impairment. Even though it has been proven that the Shen-Qi compound (SQC) can efficiently halt metabolic memory and preserve vascular endothelial cells, extensive studies need to be done to investigate if it can also change the vascular immune-inflammatory microenvironment by regulating the immune system. This will help figure out the role of stopping metabolic memory. Methods. After 4 weeks on a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…Several studies have shown that Wistar rats fed on a high-fat diet for a prolonged period develop obesity, dyslipidemia and diabetes [ 33 ]. In another study, GK rats fed on HFD for four weeks developed diabetic thoracic aortic lesion [ 34 ]. However, it is also possible to find a non-obese, diabetic person.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that Wistar rats fed on a high-fat diet for a prolonged period develop obesity, dyslipidemia and diabetes [ 33 ]. In another study, GK rats fed on HFD for four weeks developed diabetic thoracic aortic lesion [ 34 ]. However, it is also possible to find a non-obese, diabetic person.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials have shown that SQC has multiple regulatory benefits in treating diabetic patients by lowering blood glucose, regulating lipids, improving insulin resistance, regulating oxidative stress levels, and reducing carotid intima thickness ( 19 , 20 ). Further animal studies have shown that SQC can reduce glucose variability, ameliorate gut mucosal barrier damage, regulate gut microbiota and metabolites, protect pancreatic islet function in Goto-Kakizaki rats, and ameliorate vascular damage through mechanisms related to improved apoptosis, oxidative stress, and inflammatory microenvironment in the thoracic aorta ( 21 24 ). It also showed significant vasoprotective effects in diabetic mice and was superior to rosiglitazone ( 25 ).…”
Section: Introductionmentioning
confidence: 99%